THE ROLE OF PUPPET THEATRES IN EDUCATING THE YOUNG GENERATION IN THE SPIRIT OF LOVE FOR THE MOTHERLAND - Azamjon Abdukhalilov (International Journal of Literature and Language Studies, 2026)
This article discusses puppet theatre, which is considered a unique form of theatrical art, and its dramaturgy. It also reflects on the significance of puppet theatre performances in the upbringing of the younger generation.